Checklist and new records of Notonectidae (Hemiptera: Heteroptera: Nepomorpha) from Goiás, Brazil - Freires Barbosa, Julianna; Dias da Silva, Karina (EntomoBrasilis, 2017)
Abstract. The braziliansavannah, called Cerrado, has the richest flora among the world’s savannahs, and the State of Goiás comprises part of this biome. We present here a checklist for Goiás based on literature and specimens collected, with 18 species of Notonectidae, including new distribution records of Martarega membranacea White, 1879, and first records of Buenoa konta Nieser & Pelli, 1994; Buenoa pseudomutabilis Barbosa, Ribeiro & Nessimian, 2010; Buenoa tarsalis Truxal, 1953; Martarega bentoi Truxal, 1949 and Martarega brasiliensis Truxal, 1949 in the State. This checklist highlights a gap in the knowledge of Notonectidae and a great necessity of works with diversity of backswimmers in Goiás. Lista de espécies e registros novos de Notonectidae (Hemiptera: Heteroptera: Nepomorpha) do Estado de Goiás, Brasil Resumo. A savanna brasileira, chamada de Cerrado, possui a maior riqueza de flora dentre as savannas mundiais, e o Estado de Goiás encontra-se dentro dos limites deste bioma. Apresentamos aqui uma lista de espécies para Goiás baseada em literatura e espécimes coletados, com 18 espécies de Notonectidae, incluindo registros novos de distribuição de Martarega membranacea White, 1879, e o primeiro registro no Estado de Buenoa konta Nieser & Pelli, 1994; Buenoa pseudomutabilis Barbosa, Ribeiro & Nessimian, 2010; Buenoa tarsalis Truxal, 1953; Martarega bentoi Truxal, 1949 e Martarega brasiliensis Truxal, 1949. Esta lista destaca uma lacuna no conhecimento de Notonectidae e a grande necessidade de desenvolvimento de artigos com foco na diversidade de Notonectidae em Goiás.